Safety and Immunogenicity of a Gag-Pol Candidate HIV-1 DNA Vaccine Administered by a Needle-Free Device in HIV-1–Seronegative Subjects - Tavel, Jorge A. (2007)
OBJECTIVE: To evaluate the safety and immunogenicity of a candidate HIV DNA vaccine administered using a needle-free device. DESIGN: In this phase 1, dose escalation, double-blind, placebo-controlled clinical trial, 21 healthy adults were randomized to receive placebo or 0.5, 1.5, or 4 mg of a single plasmid expressing a Gag/Pol fusion protein. Each participant received repeat immunizations at days 28 and 56 after the first inoculation. Safety and immunogenicity data were collected. RESULTS: The vaccine was well tolerated, with most adverse events being mild injection site reactions, including pain, tenderness, and erythema. No dose-limiting toxicities occurred. HIV-specific antibody response was not detected in any vaccinee by enzyme-linked immunosorbent assay. HIV-specific T-cell responses to Gag or Pol as measured by enzyme-linked immunospot assay and intracellular cytokine staining were of low frequency and magnitude. CONCLUSIONS: This candidate HIV DNA vaccine was safe and well tolerated. No HIV-specific antibody responses were detected, and only low-magnitude HIV-specific T-cell responses were detected in 8 (53%) of 15 vaccinees. This initial product led to the development of a 4-plasmid multiclade HIV DNA Vaccine Research Center vaccine candidate in which envelope genes expressing Env from clades A, B, and C and a Nef gene from clade B have been added.